1992
DOI: 10.1111/j.1471-0528.1992.tb14475.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey of colposcopy service provided by genito‐urinary medicine in England and Wales

Abstract: Objective To investigate the expansion of colposcopy services within genitourinary medicine (GUM) in England and Wales since 1985. Design Data collected by postal and verbal communication from 189 genitourinary medicine clinics in England and Wales in January 1990. Subjects Consultant and junior genito‐urinary physicians practising colposcopy. Main outcome measures Number of clinics providing colposcopy service; indication for colposcopy, treatment facilities available, waiting lists an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A recent survey of eolposcopy service provided by genito-urinary medicine in England and Wales found that 60 out of 189 clinics contacted provided a colposcopy service [4], Wart contacts were routinely offered colposcopy in 21 (out of 55) clinics. In the current study, cervical cytology detected only 31% of the cervical epithelial abnormalities identified at colposcopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey of eolposcopy service provided by genito-urinary medicine in England and Wales found that 60 out of 189 clinics contacted provided a colposcopy service [4], Wart contacts were routinely offered colposcopy in 21 (out of 55) clinics. In the current study, cervical cytology detected only 31% of the cervical epithelial abnormalities identified at colposcopy.…”
Section: Discussionmentioning
confidence: 99%
“…In women with visible anogenital warts, the incidence of biopsy-proven koilocytosis or cervical intraepithelial neoplasia (CIN), is reported from 36 to 78% [1 -3]. The presence of external anogenital warts suggests a high risk for cervical epithelial abnormalities, and is accepted in many centres as an indication for colposcopy [4].…”
Section: Introductionmentioning
confidence: 99%
“…25 By 1990, 60 out of 189 clinics provided a colposcopy service. 6 In 1988 the UK National Health Service (NHS) Cervical Screening Programme of computerised call and recall for women registered with general practitioners, aged 20 to 64 years, was introduced. By March 1995, 85.7% of such women had been screened within the previous five years.7 It has been estimated that this screening has prevented thousands of cases of invasive cervical cancer.…”
mentioning
confidence: 99%